PENGARUH TINGKAT PENGETHUAN TERHADAP PERILAKU MENJAGA KEBERSIHAN ORGAN GENETALIA EKSTERNA PADA SISWI SMAN 12 KABUPATEN TANGERANG - Warsyena, Riska; Wibisono, Wibisono (Nusantara Hasana Berdikari, 2021)
Adolescence or adolescence is the time of rapid changes in terms of physical, cognitive and psychosocial or behavioral growth. Some problems also occur in teenagers, one of which is on the health of the reproductions. Objectives: The purpose of this research is to know the influence of knowledge on the behavior of maintaining the hygiene of the external genitalia organ in the students of Sman 12 Tangerang regency. Method: The method used is The method used is quantitative. The research design used in this study is a correlation description. The design that researchers use is cross sectional. The research design used in this study is a correlation description. The design that researchers use is cross sectional. The population in this study was 76 students of SMAN 12 Kabupaten Tangerang. Sampling techniques use Total sampling. Results: The majority of 17-year-old respondents were 29 students (38.2%), the majority of whom were in class XII with 36 students (51.3%). Most of the respondents had a good level of knowledge in maintaining the cleanliness of the genetalia as much as 39 respondents (51.3%). While on the behavior in maintaining the hygiene of the organ portion of Genetalia A majority of respondents has a good behaviour of 45 respondents (59.2%). The results of the chi-square statistical test were obtained that the P-value value was 0.040 which means that the < 0.05 conclusions: There is a significant relationship between the students ' knowledge with the behavior of maintaining the hygiene of the external genitalia organ. In addition, the results of the calibration test were obtained that the value of the calibration of 0.263 can be interpreted as a medium relationship. It is expected from teenagers maintain the hygiene and health of genital organs especially external parts.